Potensi dan Daya Dukung Pantai Labuhan Haji Dalam Pengembangan Kawasan Pariwisata di Kabupaten Lombok Timur - Hafizin, Hafizin; Adhika, I Made; Sunarta, I Nyoman (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2018)
Labuhan Haji Beach is one of the tourism area in Lombok Timur Regency who more visited by domestic tourist. The development tourism area required data and informations about conditions of environment. The objective of this  research is to analyze conditions of environment Labuhan Haji beach based on the some of hidro oceanography and beach morphology aspect, Tourism appropriateness index (Indeks Kesesuaian Wisata/IKW) and carrying capacity (Daya Dukung Kawasan/DDK). The hidro oceanography and beach morphology aspect is the type, the width, the material of bottom waterworks, the current speed, the slope of beach, the brightness, the wave, the land cover beach, the dangerous of biota, and the fresh water supply. This research is qualitative descriptive with survey method. There area 21 quays investigated in this research. The data gathered based on the parameter in each quay are then analized using Tourism appropriateness index (Indeks Kesesuaian Wisata/IKW) which is agreed with beach tourism appropriateness matrix. Based on the data gained from each quay, it can be concluded that all the investigated quays area categorized very appropriate. The results of analysis Tourism Appropriateness Index (Indeks Kesesuaian Wisata/IKW) for recreation area is 85-91% and swim area is 81-87% the quays area categorized very appropriate and boatting area is 59-84%. This mean that all the area in well conditions for tourism activity with maximum carrying capacity 240 person/day.